The Efficacy of Fish Scales as Bone Graft Alternative Materials - Abdul Gani Soulissa; Irene Nathania (Scientific Dental Journal, 2018)
Background: Bone graft application is a therapy that could be used to repair bone and minimize bone resorption. However, current bone graft materials carry risks for the recipient. Studies on alloplast, which can be found in fish bones and scales have been developed in the past few years. Objectives: This study aimed to determine the efficacy of hydroxyapatite powder from white barramundi (Lates calcarifer) fish scales as bone graft material in the mandibular defect regeneration of rats. Methods: This experimental laboratory study utilized 24 male Sprague-Dawley rats aged 16 weeks as test subjects, where 12 were used for control groups and the other 12 were used as the experimental group. All were given bone defects of 3 mm on the right mandible, split into 6 groups of 4 (3 experimental and 3 control groups), and the groups were observed for 2, 4, and 6 weeks respectively. The surgery results were assessed by radiography and histopathologic analysis. Result: Radiography results showed that the highest bone growth was found in the 6 weeks treatment group with 100% growth, followed by the 4 weeks treatment group with 88.89% growth, and last was the 2 weeks treatment group with 66.67% growth. The Mann-Whitney test showed that there is a significant difference between pre- and post-intervention (p >0.05). Histopathologic analysis showed the presence of osteocytes and osteoblasts in the 6 weeks treatment group. Conclusion: It can be concluded that hydroxyapatite powder from white barramundi fish scales can be used as a bone graft alternative material.